Immediate changes in blood pressure during intravitreal anti-VEGF agents' applications in exudative age-related macular degeneration patients - SEVİK, MEHMET ORKUN; ŞAHİN, ÖZLEM (SPRINGER, 2020)
Purpose To determine the short-term changes in systemic arterial blood pressure (SABP) during intravitreal anti-vascular endothelial growth factor (anti-VEGF) injection in patients with exudative age-related macular degeneration (ARMD). Materials and methods This study retrospectively reviewed the data of 550 patients with exudative ARMD, who received intravitreal anti-VEGF (bevacizumab or ranibizumab; selected randomly) injections. Patients with hypertension on medication with antihypertensive drugs were assigned to the hypertension group (HTG; n = 278); those with normal blood pressure and not on antihypertensive drugs were assigned to the normotensive group (NTG; n = 272). The SABP levels were measured 30 min before anti-VEGF injection (baseline = B), during anti-VEGF injection (DI), as well as 30th (I30) and 60th (I60) min after anti-VEGF injection. Results Both groups had significantly higher systolic blood pressure (SBP) at DI than that of the baseline values (p < 0.001), whereas the diastolic blood pressures (DBP) increased significantly at DI, I30, and I60 compared with baseline (p < 0.001). In NTG, SBP was significantly higher in patients at I30 (p = 0.019), whereas that in HTG was significantly higher at all measurements (p < 0.05) only in patients who received intravitreal bevacizumab injection. Conclusion Our study results show that intravitreal anti-VEGF injection is associated with a short-term increase in SABP. To prevent potential systemic complications during anti-VEGF administration, the systemic status of patients with ARMD should be evaluated before the injection and those with a risk of high SABP during injection should be closely monitored.
Keywords: Anti-vascular endothelial growth factor; Bevacizumab; Ranibizumab; Systemic arterial blood pressure; ENDOTHELIAL GROWTH-FACTOR; BEVACIZUMAB AVASTIN; ANGIOGENESIS; SAFETY